2000
DOI: 10.1034/j.1600-0676.2000.020003234.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II genotypes associated with chronic hepatitis C virus infection and response to α‐interferon treatment in Poland

Abstract: The results confirm the negative association between chronic HCV and DQB1*0301 and identify two novel genetic associations. In particular, the DRB1*0701-DQA1*0201-DQB1*02 haplotype is associated with both chronic infection and response to alpha-interferon. Interestingly, the same haplotype is reportedly associated with non-response to hepatitis B vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 0 publications
2
35
0
3
Order By: Relevance
“…The results of different studies confirm the negative association between chronic HCV infection and DQB1*0301 allele (12). Association of DQB1*0301 allele with natural clearance of HCV is mentioned by many authors in original studies and reviews (10,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The other allele described as being important in patients who clear HCV spontaneously is DRB1*1101 (13,16,18,(20)(21)(22)(23)(24).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…The results of different studies confirm the negative association between chronic HCV infection and DQB1*0301 allele (12). Association of DQB1*0301 allele with natural clearance of HCV is mentioned by many authors in original studies and reviews (10,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The other allele described as being important in patients who clear HCV spontaneously is DRB1*1101 (13,16,18,(20)(21)(22)(23)(24).…”
Section: Introductionsupporting
confidence: 67%
“…Our study focused more on one internal factor, namely, some HLA II class alleles, that could contribute to spontaneous resolution of HCV infection in population in Latvia. The results of different studies confirm the negative association between chronic HCV infection and DQB1*0301 allele (12). Association of DQB1*0301 allele with natural clearance of HCV is mentioned by many authors in original studies and reviews (10,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionsupporting
confidence: 64%
“…4,16,17,25,32,35,39,41,52 One study, however, reported an opposite effect for DQB1*0301. 48 Several of these studies on susceptibility to HCV compared individuals with chronic HCV infection to healthy controls. The use of healthy individuals poses a study design problem, as an estimated 54-86% of these controls, if exposed to the HCV, would develop chronic infections, while the others experience viral clearance.…”
Section: Susceptibility To Persistent Hcv Infectionmentioning
confidence: 99%
“…62 Response to anti-HCV therapies A total of 32 studies addressed the potential role of genetics in the response to interferon therapy or variations in viral load. 16,24,27,37,39,[46][47][48][49] Unlike studies of susceptibility to HCV, the majority of studies have concerned regions outside the MHC, with an emphasis on single-nucleotide polymorphisms (SNPs). Three main outcomes are commonly examined in studies of the response to anti-HCV therapies: (1) Sustained responsenow commonly defined virologically as having undetectable serum HCV-RNA levels at 6 months after the discontinuation of treatment.…”
Section: Susceptibility To Persistent Hcv Infectionmentioning
confidence: 99%
“…Fanning et al (2001) reported that individuals who possess the alleles DRB1*0701 and/or DQB1*0201 have a relatively stable viral load over time. Also DRB1*07 and DQB1*02 were found by Wawrzynowicz-Syczewska et al (2000) in responsive patients and Jiao and Wang (2003) found a higher response rate to IFN in patients with the HLA-DRB1*07 allele where Martinetti et al (2006) reported that DRB1*13 allele was significant in protection from chronic HCV especially the protection from vertical transmission in infants born to HCV positive mothers.…”
Section: Discussionmentioning
confidence: 99%